Ancient Christian commentary on Scripture ; NT v.IX - Gorday, Peter (Downers Grove, IL IVP, 2000)
Contents : v. IX : Colossians, 1-2 Thessalonians, 1-2 Timothy, Titus, Philemon. Includes bibliographical references and indexes.
Keywords: Bible. N.T. Colossians -- commentaries; Bible. N.T. Thessalonians -- commentaries; Bible. N.T. Timothy -- commentaries; Bible. N.T. Titus -- commentaries; Bible. N.T. Philemon -- commentaries; Bible. N.T. Epistles -- criticism, interpretation, etc. -- history -- early church, ca.30-600 -- sources; Fathers of the church